Perceptions of value intertwined: the perceived value of Business in the Community’s Corporate Responsibility Index:‘assemblages of worth’ in evolution - Kirk, Jacqueline Louise (2018)
In recent years there has been an increase in metrics and indices measuring corporate social responsibility (CSR) (SuatainAbility, 2010; IBE, 2013). In legitimating the premise of these metrics focus has centred on the effects of inclusion, either in regard to financial impact for the firm (Beurden and Gössling, 2008; Griffin and Mahon, 1997), validity in gaining and conveying legitimacy (Chatterji et al, 2007; Agle and Kelly, 2001; Font et al, 2012; Graafland et al, 2004), or social impact in promoting responsible business practices (Slager et al, 2010; Slager, 2012; Adam and Shavit, 2007; Scarlet and Kelly, 2009). Yet, arguably these tools are now institutionalised elements of CSR (Waddock, 2008), and thus focus is no longer centred on gaining legitimacy, but rather on retaining it, as they ‘face the need to evolve…in the context of the changing demands of constituents and environmental change’ (Durand & McGuire, 2005, p.168). However, little is known about how these effects (financial, social and validity) impact the valuation dynamics associated with participation in these tools over time. This thesis aims to fill this gap by exploring processes of legitimation and critique of participation in Business in the Community’s Corporate Responsibility Index (BiTC’s CRI). Through the lens of Boltanski and Thévenot’s economies of worth (2006), the thesis examines the ‘orders of worth’ drawn upon in legitimating and critiquing participation in the CRI over time.